BEBERAPA MASALAH TENTANG PROSES ALIH DEBITUR DALAM PERJANJIAN KREDIT KEPEMILIKAN RUMAH DI BANK TABUNGAN NEGARA CABANG SAMARINDA - Elipen Pardesi (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACK National development based on Pancasila and the 1945 Constitution is essentially the whole person development and construction of all the people of Indonesia.With the growing level of people's lives, it also increased their daily needs. Accordingly, the problem arises when people are not able to buy a house in cash due to limited financial capacity, while more urgent housing needs. The fact that there is in our society are largely classified societies with low levels of the economy.Intervention of the government in the fulfillment of housing facilities is needed. Because of very rapid population growth also means the increasing need of homes. While the provision of housing needs increasingly difficult by the community, this was due to the limited land and increasing land prices from year to year, so that it results in the need for the provision of shelter or housing requires no small cost.